Analysis Of Rain-Induced Landslide In Volcanic-Collu Vial Deposits in Kalibawang irrigation channel,Yogyakarta, indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
The maw objective of this research is to investigate the in/luences of slope stratigraphy and lrydrology on â¢aininduced landslides in the iwIcanic-colluvial deposit deposits at Kalibawang Irrigation Channel Section KM 15.9, Kulon Progo. Yogyakarta. Indonesia, Therefore, some engineering geological investigations were carried out. The research method involved field monitoring, some laboratory tests and desk study to analyze the landslide mechanism, It was .found that slope stratigraphy condition was the most significant control of landslide in the study area, The landside occurred due the creeping (slow movement) within the colluvial deposits, in particular at the laver of tuff which was overlain by the lenses of tufaceous breccias, ciaystone-mudstone hreccias and claystone-mudstone-andesitic hreccias, tulkeous claysrone breccias and sandy clay. The research came: with the conclusions that stratigraphy conditions of the colluvial deposits and the underlain more impermeable mudstone significantly control the geotechnical and slope hydrological conditions in response to the rainfall, until then the creeps occur. In addition, creeps in the upper and nriddle foot-slope occur because of the movement ft a thin tuff layer, which exists within the colluvial deposits of tufaceous hreccias. kforeover, the relatively low permeability optic colherial materials brings about to the Mai- of groundwater table fluctuations and the initiations of creeping